DENTAL CONSIDERATIONS FOR THE TREATMENT OF PATIENTS WITH DIABETES - A REVIEW - Ms., Madhumithaa Sivarajan; S., Raghunandhakumar; Ezhilarasan, Devaraj (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes Mellitus (DM) is one of the most prevalent diseases that dentists encounter because of its high global prevalence. It is diagnosed by frequent diagnosis of fasting plasma glucose levels (reference range is 126 mg/dl or higher). Diabetes, if not controlled properly, leads to a higher risk of periodontal disease, and glycemic control and its mechanisms are still not well established. Many oral symptoms include xerostomia, sialadenitis, and burning mouth syndrome. In order to avoid the practical difficulties of dental treatment for a diabetic patient, a dentist should know the dental patient's medical history before starting the practice. Concomitantly, the treatment should be done in the morning to alleviate patients’ discomfort with their diabetic complication. The dentist must be conscious that an acute complication can occur (hypoglycemia or hyperglycemia). Furthermore, these patients suffer from delayed wound healing and major susceptibility to infections.